Development and evaluation of Alternaria blight tolerant lines in Indian mustard (Brassica juncea) - Praval Pratap; PD Meena; BK Singh; HS Meena; SS Meena; Pankaj Sharma; Rita Majumdar; Dhiraj Singh (Journal of Oilseed Brassica, 2026)
The present study was aimed to evaluate and develop Alternaria blight tolerant lines in Indian mustard[Brassica juncea (L.) Czern & Coss.]. A total of 14 Alternaria blight tolerant lines were selected from 214lines in F8 generation. Amongst the selected lines, DRMR-2803, DRMR-2805 and DRMR-2806 showed theleast per cent mean disease severity values of 11.4, 10.4 and 9.4, respectively. However, only DRMR-2805exhibited seed yield/plant higher than the check variety Varuna. Per se performance of selected lines, evaluatedfor three consecutive years (2010-13), varied considerably for most yield parameters. The most pronouncedrange was obtained for plant height (203.7 - 264.5 cm), siliquae on main shoot (36.4 - 61.7), main shoot length(30.6 - 81.3 cm), and seed yield per plant (5.4 - 39.7g); number of primary branches/plant (7.1 -12.2) siliqualength (3.0 - 4.5 cm), number of seeds/siliqua (12.4 - 15.6), 1000 seed weight (2.3 - 5.4g), and % oil content(39.6 - 41.6) exhibited narrow range of variation. RAPD analysis of selected Alternaria blight tolerant lines,along with tolerant, (PHR-2 and PAB- 9511), and susceptible (Varuna) checks, clearly distinguished theindividual lines to their available pedigree data. Highly promising tolerant lines identified in the present studymay be used as potential donors for transferring Alternaria blight tolerance in high yielding mustard varieties.The advanced Alternaria blight tolerant breeding line DRMR-2805 showing seed yield/plant almost at parwith check variety Varuna must be released as a variety after multi-location testing.